IMPLEMENTATION OF THE BALANCED SCORECARD AS A MEASUREMENT OF PERFORMANCE ASSESSMENT AT THE SOCIAL OFFICE OF SEMARANG CITY - Canny Diah Prameswari; Mohammad Hasanudin; Ardian Widiarto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
This study aims to analyze the performance of Dinas Sosial Kota Semarang using the Balanced Scorecard method. The analytical method used is the descriptive method. The data used are the results of interviews, financial statements of budget realization, number of employees, number of employees attending training, and the value of community satisfaction surveys. The results of this study show that the performance of Dinas Sosial Kota Semarang from a financial perspective in 2019-2021 shows economic conditions with an average value of 88.83%. The performance of the internal business perspective in 2019-2021 shows a very good condition by obtaining an average score of 164.09%. The performance of the learning and growth perspective shows poor conditions by obtaining an average score of 32.94%. The performance of the customer perspective shows a very good condition by obtaining an average score of 88.25%. And the overall performance of the four perspectives shows a very good qualification with a score of 92.11% and a very successful success rate.